The glacial paleovalley of Vichigasta: Paleogeomorphological and sedimentological evidence for a large continental ice-sheet for the mid-Carboniferous over central Argentina - Valdez Buso, Victoria; Milana, Juan Pablo; di Pasquo, Mercedes; Espinoza Aburto, José Horacio (Journal of South American Earth Sciences)
We present new data on the Vichigasta Carboniferous paleovalley, a glacial trough crucial to understand the type of glaciation that affected western Gondwana during the Late Paleozoic Ice Age (LPIA). The filling of this paleovalley starts soon after the mid-Carboniferous glacial peak. Stage I represents pro-glacial lacustrine deposits with outwash, glacially rafted dropstones, mass transport deposits (MTDs) and turbidites of the trunk and a lateral tributary valley. Base-level drop created the scenario for Stage II outwash deltas and sandur deposits, with westward flow. Stage III represents a flooding at the base of the Bashkirian, characterized by typical transgressive dark shales and distal turbidites. Stage IV represents a highstand prograding turbidite wedge. We worked in a detailed terrain analysis, surveyed the scarce sedimentary record left and recovered a rich palynoflora from mudstones of Stage 3. The almost complete erosion of the fill allowed us to analyze the shape of this paleovalley and compare it to Olta and Malanzán ones. Vichigasta and Malanzán paleovalleys show similar size, a clear U-shape and regular and homogeneous width downslope, a requisite for bypass glacial paleovalleys carved in a subcrop of homogeneous composition (basement), which allow us to interpret them as outlet valleys. Olta paleovalley ranks as tributary as its capacity is only one-third of the others. We also identified a basement high over the Vichigasta valley floor that suggests the presence of a potential drumlin supporting our interpretation as a bypass glacial valley. This post-glacial flooding event is widely observed at other glacial valleys as the Olta-Malanzán herein analyzed and others like Las Lajas and Quebrada Grande. The new data from Vichigasta paleovalley reinforce the hypothesis of a large ice-sheet located to the east of the craton. Fil: Valdez Buso, Victoria. University Of Aberdeeen; Reino Unido. University of Aberdeen; Reino Unido Fil: Milana, Juan Pablo. Consejo Nacional de Investigaciones ...